Real Dragons! - Szymanski, Jennifer (Washington, D.C. : National Geographic Kids, 2017)
Find out about dragon-like critters in this new Co-reader from National Geographic Kids. Think dragons exist only in fairy tales? Think again! Meet huge komodo dragons, flying lizards, and all sorts of amazing creatures that really are stranger than fiction.
ch. 1 Are Dragons Real? -- Your Turn! -- ch. 2 Dragon Superpowers -- ch. 3 Big Dragons -- Your Turn! -- ch. 4 All Kinds of Dragons.
Junior primary school age.
Keywords: Animals -- Juvenile literature; Dragons -- Juvenile literature; Readers (Primary)